A formal investigation of inequalities in health behaviours after age 50 on the Island of Ireland - Eibhlin Hudson; David Madden; Irene Mosca (University College Dublin, UCD School of Economics, 2014)
Smoking, low physical activity and frequent alcohol consumption may have substantial health risks in terms of disease, quality of life and mortality. Understanding inequality in relation to these behaviours among older people is important in the context of a rapidly ageing population. In this study, we examine income-related inequality in relation to these three key health behaviours using data on older adults from both the Republic of Ireland and Northern Ireland. We employ concentration indices and decompose them to determine the factors which contribute most to inequality. We then examine whether differences exist between the two regions. We find that smoking and low physical activity are more concentrated among those with lower incomes in both regions. In relation to physical activity, the magnitude of the inequality is higher for Northern Ireland. Frequent alcohol consumption is more concentrated among those with higher incomes in both regions. Self-assessed health and age tend to feature prominently for all behaviours in terms of contribution to inequality. Marital status and labour market status tend to play a less pronounced role. In terms of Northern Ireland/Republic of Ireland comparisons with respect to the decompositions, probably the biggest difference is to be observed in the greater role accorded to labour market status in the Republic. For the other factors, the orders of magnitude are reasonably similar. This suggests that in many cases it may be the same underlying factors which lie behind income related inequalities.
Keywords: I14; J14; 330; inequality; health behaviours; older adults; Republic of Ireland; Northern Ireland